Correlation of Verbal Abuse to Children's Self-Confidence - Umi Harti; Pujiarto (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
The study aims to analyze the relationship between verbal violence and self-confidence of children 4-5 years old in Wonosari Village, Kebumen District. The method used in this study is a survey method with a correlational approach. The independent variable or independent variable in the study is verbal violence. The variable tied to this study is confidence. The population in this study amounted to 2816 children aged 4-5 years along with their parents in kindergarten family planning located in Kebumen District. The author uses a simple random sampling technique because the population in this study is homogeneous using the slovin formula. Based on the slovin formula, the sample value was obtained at 96.5 or rounded to 96 parents of children. In this research, the data collection instrument is in the form of questionnaires. Test the hypothesis in this study using the Pearson Product Moment test using SPSS v22 software. The results showed a correlation coefficient value of -0.551, which shows that the relationship is negative and strong. Based on the results, the significance value between the variables of verbal violence and self-confidence has a significance value of 0.003 < 0.05, which means there is a significant correlation. So it can be concluded that the higher the level of verbal violence experienced by children, the lower the trust in children aged 4-5 years in Kebumen sub-district.